Obesity and arterial hypertension. Part II: features of antihypertensive therapy in obese patients - S. V. Nedogoda; I. N. Barykina; T. A. Chalyabi; L. V. Butrina; U. A. Brel; G. V. Mazina; E. A. Podolskaya (Кардиоваскулярная терапия и профилактика)
The review is devoted to the features of antihypertensive therapy (AHT) in arterial hypertension combined with obesity. Pathogenesis of blood pressure increase in obesity is emphasised. The authors analyse the safety of various antihypertensive medication classes in these patients. The most effective AHT schemes to combine with weight-reducing medications are described.